Avaliação da citotoxicidade de solução de ácido hipocloroso obtida a partir de dispositivo eletrolítico – estudo in vitro - Ferreira, Eduarda Rizzon (2023)
The objective of the present study was to evaluate, in vitro, the cytotoxicity of a hypochlorous acid solution obtained from an electrolytic device, at a concentration of 250 ppm, in comparison with sodium hypochlorite at a concentration of 2.5%. The cytotoxicity test was performed using the MTT assay, which corresponds to a colorimetric test used to assess cell viability. The groups used to carry out this study were: G1 – distilled water (control); G2 – 2.5% sodium hypochlorite (2.5% NaOCl) and G3 – 250ppm hypochlorous acid (250 ppm HClO). After preparing the cell culture medium, 100 uL of the same treatment groups already mentioned were added individually to the wells containing the medium, being incubated for a period of 3 minutes. All experiments were performed in triplicate and cell viability percentages were calculated relative to cell controls. Cytotoxicity was analyzed by one-way ANOVA followed by Tukey's post-hoc test (α=0.05). The results of the cytotoxicity test revealed that all chemical substances tested were statistically different when compared to the control group. However, the G3 group was less cytotoxic than the G2 group. It can be concluded that hypochlorous acid was less cytotoxic when compared to sodium hypochlorite, in addition to being as effective as bacterial reduction.